Pediatric Secrets - Polin, Richard A. (Hanley & Belfus, 2001)
Pediatric Secrets is an easy-to-read, best-selling volume in the Secrets Series, perfect for use in clerkships, for board prep, or as a handy clinical reference. Richard A. Polin, MD and Mark F. Ditmar, MD present essential questions and answers to help you better meet the challenges you face every day.